2006
DOI: 10.1039/b612509n
|View full text |Cite
|
Sign up to set email alerts
|

Trace metal bioaccumulation in eight common coastal Australian polychaeta

Abstract: Whole tissue trace metal concentrations of ten metals in eight common coastal Australian polychaete species collected from uncontaminated locations were measured. The mean concentration range for each trace metal was: Mn: 2.6-13 microg g(-1); Co: 0.8-4.6 microg g(-1); Cu: 3.4-26 microg g(-1); Zn: 47-225 microg g(-1); As: 18-101 microg g(-1); Se: 2.2-20.4 microg g(-1); Ag: 0.03-2.5 microg g(-1); Cd: 0.07-17 microg g(-1); Hg: 0.08-0.88 microg g(-1) and Pb: 0.09-3.2 microg g(-1)dry mass. Principal components anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 21 publications
2
5
0
Order By: Relevance
“…Comparing accumulation of metals in Polychaete species in this study with other studies in the Black Sea (Table 6), it can be seen that Waring et al (2006) recorded higher concentrations of Hg and Cd in Australonuphis parateres of Australia coasts, whereas Dora et al (2007) (Andreev et al, 1994) and high Zn values were recorded in Perinereis cultrifera from Venetian lagoon-Italy (Volpi Ghirardini et al, 1999). Our values of these metals were lower than those in other studies (Table 6).…”
Section: Discussionsupporting
confidence: 47%
“…Comparing accumulation of metals in Polychaete species in this study with other studies in the Black Sea (Table 6), it can be seen that Waring et al (2006) recorded higher concentrations of Hg and Cd in Australonuphis parateres of Australia coasts, whereas Dora et al (2007) (Andreev et al, 1994) and high Zn values were recorded in Perinereis cultrifera from Venetian lagoon-Italy (Volpi Ghirardini et al, 1999). Our values of these metals were lower than those in other studies (Table 6).…”
Section: Discussionsupporting
confidence: 47%
“…G . caespitosa is a filter-feeding species, which is able to accumulate hazardous substances through the uptake of suspended particulate matter during the water exchange involved in foraging activities [3, 7]. …”
Section: Introductionmentioning
confidence: 99%
“…gemineoa maximises its exposure to suspended hazardous substances in the ambient water as they process large volume of water during foraging activities [ 7 ]. Waring et al [ 8 ] demonstrated that this species had a higher capacity to accumulate toxic heavy metals including mercury, silver and zinc compared with several other marine polychaetes tested ( Australonereis ehlersi , Australonuphis parateres , Lumbrinereis spp., Marphysa spp., Notomastus estuaries , Scoloplos simplex , and Sigalion spp.). In reproductive terms, adult male and female G .…”
Section: Introductionmentioning
confidence: 99%